Cover Picture: Titanium Nitride Nanocrystals on Nitrogen‐Doped Graphene as an Efficient Electrocatalyst for Oxygen Reduction Reaction (Chem. Eur. J. 44/2013). Issue 44 (16th October 2013) - Liu, Mengjia; Dong, Youzhen; Wu, Yongmin; Feng, Hongbin; Li, Jinghong
<x xml:space="preserve">Abstract</x> An efficient electrocatalyst for the oxygen reduction reaction (ORR) based on a TiN/nitrogen‐doped graphene hybrid, generated through facile grain nucleation and growth of titanium nitride (TiN) nanoparticles on simultaneously generated nitrogen‐doped graphene (NG) sheets under ammonia annealing, is described by J. Li et al. in their Full Paper on p. 14781 ff. Oxygen and water molecules react on the hybrid in a four‐electron pathway. Experimental results indicate that the excellent catalytic activity is ascribed to the synergistic chemical coupling effects between TiN and NG.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>